Comprehensive Identification and Alternative Splicing of Microexons in Drosophila - Pang, Ting-Lin; Ding, Zhan; Liang, Shao-Bo; Li, Liang; Zhang, Bei; Zhang, Yu; Fan, Yu-Jie; Xu, Yong-Zhen (Frontiers in Genetics, 2021)
Interrupted exons in the pre-mRNA transcripts are ligated together through RNA splicing, which plays critical roles in the regulation of gene expression. Exons with length ≤30 nt are defined as microexons that are unique in identifications and gene functions. However, due to difficulties in mapping short segments from sequencing reads, microexons especially shorter than 8 nt, have not been well studied in many organisms. Here, we analyzed mRNA-seq data from a variety of Drosophila samples by a new developed bioinformatic tool, ce-TopHat. In addition to the Flybase annotated, 465 new microexons were identified. Differentially alternatively spliced (AS) microexons were investigated between the Drosophila tissues (head, body and gonad) and genders. Most of the AS microexons are found in the head, as well as two AS microexons were identified in the sex-determination pathway gene fruitless.